Pemanfaatan Jamur Tiram untuk Kebutuhan Pangan sebagai Kearifan Lokal Masyarakat Perkotaan - Icuk Muhammad Sakir; Lishapsari Prihatini; Indah Pusnita; Asi Larasaty (Universitas Pahlawan Tuanku Tambusai, 2022)
This service aims to determine the use of oyster mushrooms for food needs as local wisdom for urban communities. The method used with an ethnographic approach is to describe in detail the oyster mushroom cultivation technique for the community in Kalidoni District, Palembang City. The process of cultivating oyster mushrooms from start to harvest takes about one month. Baglog from sawdust used can last for 7 months, then it must be replaced with new planting media. The time interval for the first harvest and the next harvest takes 2-3 days. Mushroom yields will be maximized if you regularly water three times in one day. Production of oyster mushrooms for one baglog media, can produce 0.5 kg to 1 kg of mushrooms. The mushroom harvesting system is carried out from the base of the stem because the remaining stems can rot. Harvesting is done every day or every few days depending on the distance from which the polybags are opened. The one baglog produces about 1 kg of mushrooms at a price of Rp.25,000 to Rp.30,000/kg.